2004
DOI: 10.1007/s00330-004-2338-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical, magnetic resonance and evoked potentials data in a case of valproic-acid-related hyperammonemic coma

Abstract: Magnetic resonance (MR) multimodality evoked potentials (MEPs) and clinical findings were correlated in a 47-year-old epileptic man in whom parenteral valproic acid (VPA) therapy induced severe comatose hyperammonemic encephalopathy without biological signs of hepatotoxicity (or hepatocytic dysfunction). Although the plasma VPA level remained within a normal therapeutic range, the ammoniemia increased to a toxic peak level at 411 micromol/l 24 h after symptom onset, requiring VPA therapy discontinuation. Brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 21 publications
1
6
1
Order By: Relevance
“…Until today, the highest ammonia value of 411 mmol/l has been reported in a 47-year-old man who came up with a completely reversible valproate-induced encephalopathy. In contrast to our report, this patient’s MRI disclosed a significant brain edema followed by cerebral atrophy (Hantson et al 2005). …”
Section: Discussioncontrasting
confidence: 99%
“…Until today, the highest ammonia value of 411 mmol/l has been reported in a 47-year-old man who came up with a completely reversible valproate-induced encephalopathy. In contrast to our report, this patient’s MRI disclosed a significant brain edema followed by cerebral atrophy (Hantson et al 2005). …”
Section: Discussioncontrasting
confidence: 99%
“…However, in cases of profound coma and impending death, this pattern is replaced by further slowing of delta frequencies and general flattening of background activity. 8,13,14 Profound slowing and attenuation of background activity on our patient's EEG is indicative of a deep coma and correlates well with the clinical finding of decorticate posturing.…”
Section: Discussionsupporting
confidence: 76%
“…Grubben et al reported restricted diffusion on DWI in a patient with VHE discussing hyperosmolarity of the cytoplasm in astrocytes due to an excess of intracellular glutamine [3]. Hantson et al showed a case with cytotoxic edema of the cerebral cortex and vasogenic edema of the white matter and in the brain stem resembling MRI findings in patients with status epilepticus [4]. They described for the first time an involvement of the pons without decreased diffusion similar to our case.…”
Section: Discussionmentioning
confidence: 69%
“…Diffusion-weighted imaging (DWI) may show restricted diffusion [3]. Hantson et al described an involvement of the brain stem together with widespread supratentorial cortical and subcortical swelling [4]. We report a case with clinically proven VHE showing reversible hyperintense signal on MRI predominantly affecting the upper brain stem.…”
Section: Introductionmentioning
confidence: 94%